2017
DOI: 10.1371/journal.pone.0173501
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine carcinoma of the esophagus: Clinicopathological and immunohistochemical features of 14 cases

Abstract: BackgroundNeuroendocrine carcinoma (NEC) of the esophagus is a rare and highly aggressive disease but the biological features are poorly understood. The objective of this study was to analyze the clinicopathological and immunohistochemical features of NEC of the esophagus.MethodsFourteen patients diagnosed with NEC of the esophagus from 1998 to 2013 were included in this study. Clinicopathologic features, therapeutic outcomes and immunohistochemical results were analyzed.ResultsEleven out of 14 cases showed pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 16 publications
1
40
0
1
Order By: Relevance
“…Regarding the origin of esophageal NETs, Merkel cells and stem cells are reported candidates [ 22 , 23 ]. Egashira et al showed positive staining for CK20, a marker of Merkel cells, in 14.3% of esophageal MANECs and suggested c-kit and p53 to be potential markers of the origin of NEC cells [ 22 ]. On the other hand, it was suggested that gastric NECs arise from adenocarcinomas rather than from non-neoplastic neuroendocrine cells [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the origin of esophageal NETs, Merkel cells and stem cells are reported candidates [ 22 , 23 ]. Egashira et al showed positive staining for CK20, a marker of Merkel cells, in 14.3% of esophageal MANECs and suggested c-kit and p53 to be potential markers of the origin of NEC cells [ 22 ]. On the other hand, it was suggested that gastric NECs arise from adenocarcinomas rather than from non-neoplastic neuroendocrine cells [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal NECs are a very rare cause of dysphagia and represent only 0.4%-2.0% of all esophageal malignancies. [2] Additional uncommon locations are the jejunum, ileum, bladder, cervix, and prostate. [2,4] At the time of diagnosis, the prognosis is considered poor, with median survivals of 34, 14, and 5 months for those with localized, regional, and distant disease respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Additional uncommon locations are the jejunum, ileum, bladder, cervix, and prostate. [2,4] At the time of diagnosis, the prognosis is considered poor, with median survivals of 34, 14, and 5 months for those with localized, regional, and distant disease respectively. [5] Treatment is subsequently guided based on the classification of limited disease (LD) versus extended disease (ED).…”
Section: Discussionmentioning
confidence: 99%
“…NENs pažeráka sú pomerne vzácne a zriedkavé nádory, s incidenciou 0,05-7,6 % zo všetkých malignít pažeráka [48]. Tieto ná-dory rastú prevažne v dolnej tretine pažeráka, často sú asociované s Baretovým ezofágom [49].…”
Section: Nens Pažerákaunclassified